PERAN PUSTAKAWAN DALAM MEWUJUDKAN LAYANAN PERPUSTAKAAN BERBASIS INKLUSI SOSIAL MELALUI PROGRAM PROLITERASIKU - Hesthiyono Suko Adhi (Jurnal IPI (Ikatan Pustakawan Indonesia), 2018)
The library is a center of information literacy that is provided to the public regardless of ethnicity, religion, race or class. Probolinggo District Public Library seeks to change the library paradigm, from conventional transformation to a library based on social inclusion services. The role of librarians in the transformation program of library development so that it is more beneficial for the community is carried out with various strategies. This has proven to have a positive impact on the library, including being able to improve the image of the library and support from various parties, both from the government and the private sector. The library transformation effort initiated by the librarian also contributed significantly to the development of human capital (human capital development) with the presence of support from the Regional Government of Probolinggo Regency. In this article the author tries to raise the ability of librarians to carry out various strategies for library development so that the Library can become a regional priority program in Probolinggo Regency.